Non-Obstructive Azoospermia with Hypergonadotropic Hypogonadism without a Significant Abnormalities in the Physical Examination - Raditya Ibrahim; Cennikon Pakpahan; Pety Narulita (Universitas Airlangga, 2022)
Background: Around 10 % of infertile men and 1 percent of all males have azoospermia. There are two types of azoospermia, which are obstructive and non-obstructive azoospermia. Non-obstructive azoospermia's main mechanism is because the testes fail to produce the sex hormone and induce spermatogenesis (primary testicular failure). Case: A patient is 28 years old and has a job as a car paint worker. He came with the chief complaint of infertility since two and a half years ago. He and his wife were having intercourse 3-4 times a week. Past medical history is unremarkable. His wife’s medical history is also unremarkable. Physical examination and ultrasound of the testes are normal. The semen analysis in this patient was azoospermia for 2 different times in the span of 2 weeks with no abnormalities in the accessory gland. Hormonal profiles results are testosterone level 2,32 ng/mL and FSH 15,03 mIU/mL, which indicatehypergonadotropic hypogonadism. The patient was suggested to evaluate further (complete hormonal profile, karyotyping analysis, and Y-Chromosome microdeletion) and educate about the possibility to conceive with assisted reproductive technology (ART). Discussion: Hypergonadotropic hypogonadism is a challenging case that needs a complete assessment such as complete hormonal profile, karyotyping analysis, Y-chromosome microdeletion analysis, and also, in this case, the paint thinner exposure in the workplace is needed to be considered. The chance of normal conception is very small, and the assisted reproductive procedure is necessary. Conclusion: Some abnormalities are usually present in the physical examination of azoospermia patients. This case convinces us of the importance of thorough history taking and other investigations. Managing this patient will be challenging, with the goal of the therapy is to achieve spermatogenesis to be able to use the spermatozoa available for ICSI.